Family Justice between the Individual Judge and the Collective Formation - Belmohoub, Mohamed Tahar (Journal of Legal Studies and Researches, 2022)
The family is the basic unit for the construction of society. The legislature attaches great importance to the family and has paid special attention to it through the provisions of the family Code and the Code of Civil and Administrative Procedure. Given the specificity of family disputes, this paper examines the extent to which disputes can be decided by a collective formation of judges at the court of first instance.